Analysis of the Asian Seabass Transcriptome Based on Expressed Sequence Tags - Xia, Jun Hong (Oxford University Press, 2011)
Analysis of transcriptomes is of great importance in genomic studies. Asian seabass is an important fish species. A number of genomic tools in it were developed, while large expressed sequence tag (EST) data are lacking. We sequenced ESTs from nine normalized cDNA libraries and obtained 11 431 high-quality ESTs. We retrieved 8524 ESTs from dbEST database and analyzed all 19 975 ESTs using bioinformatics tools. After clustering, we obtained 8837 unique sequences (2838 contigs and 5999 singletons). The average contig length was 574 bp. Annotation of these unique sequences revealed that 48.9% of them showed significant homology to RNA sequences in GenBank. Functional classification of the unique ESTs identified a broad range of genes involved in different functions. We identified 6114 putative single-nucleotide polymorphisms and 634 microsatellites in ESTs. We discovered different temporal and spatial expression patterns of some immune-related genes in the Asian seabass after challenging with a pathogen Vibrio harveyi. The unique EST sequences are being used in developing a cDNA microarray to examine global gene expression and will also facilitate future whole-genome sequence assembly and annotation of Asian seabass and comparative genomics.